2016
DOI: 10.1080/00288330.2015.1078821
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MVRenaheavy fuel oil and dispersed oil on yellowtail kingfish early life stages

Abstract: The grounding of the MV Rena has highlighted the lack of information concerning the effects of oil-related compounds on New Zealand marine life. Yellowtail kingfish (YTK), Seriola lalandi, embryos were exposed in static incubations to the wateraccommodated fraction (WAF) of Rena heavy fuel oil as well as a similar preparation treated with the commercial dispersant Corexit 9500. Mortality in WAF treatments generally increased in association with total polycyclic aromatic hydrocarbon (tPAH) concentration over a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The findings of Muncaster et al (2016) are supported by those of Koyama & Kakuno (2004) that chemically dispersed HFO was more toxic to juvenile red sea bream than dispersant or oil alone. Adams et al (2014) discovered that chemically dispersed HFO was more toxic to Atlantic herring embryos than the oil itself and that the increased toxicity was rather due to a higher degree of bioavailability of the dispersed oil than to changes in hydrocarbon toxicity.…”
Section: Dispersantsmentioning
confidence: 64%
See 2 more Smart Citations
“…The findings of Muncaster et al (2016) are supported by those of Koyama & Kakuno (2004) that chemically dispersed HFO was more toxic to juvenile red sea bream than dispersant or oil alone. Adams et al (2014) discovered that chemically dispersed HFO was more toxic to Atlantic herring embryos than the oil itself and that the increased toxicity was rather due to a higher degree of bioavailability of the dispersed oil than to changes in hydrocarbon toxicity.…”
Section: Dispersantsmentioning
confidence: 64%
“…The authors suggest that this may be related to greater dissolution of PAHs in chemically dispersed oil due to the formation of micro-droplets and that the concentration of dispersant as well as the types of oil and dispersant used may all influence total PAH concentrations. Muncaster et al (2016) also report that the concentration of dispersant used in their study likely contributed to the complete mortality of the embryos tested, although the ratio of dispersant to oil was in accord with the recommended guidelines, i.e. 1:20.…”
Section: Dispersantsmentioning
confidence: 92%
See 1 more Smart Citation
“…These assays indicated that the effects of HFO on its own are likely to have been relatively minor for adult fishes and crustaceans (Webby & Ling 2016). In contrast, for larval fish, ecologically relevant PAH concentrations caused some morbidity and developmental abnormalities (Muncaster et al 2016). For all organisms and life stages examined, the addition of Corexit 9500 increased the uptake and toxicity of PAHs, leading to greater mortality and amplified sub-lethal effects.…”
Section: The Impactsmentioning
confidence: 97%
“…It was not possible to conduct in situ monitoring during the periods where oil was being released from the stricken vessel or in the two instances when the oil dispersant Corexit 9500 was being used to combat the oil slick at sea (Maritime New Zealand 2013). However, ecotoxicological assays were done a posteriori to examine lethal and sub-lethal effects of the water-accommodated fraction of HFO and Corexit 9500 on adult and larval fish and rock lobster (Muncaster et al 2016;Webby & Ling 2016). These assays indicated that the effects of HFO on its own are likely to have been relatively minor for adult fishes and crustaceans (Webby & Ling 2016).…”
Section: The Impactsmentioning
confidence: 99%